Comparison of relative oxycodone consumption in surgical pleth index-guided analgesia versus conventional analgesia during sevoflurane anesthesia: A randomized controlled trial. Issue 35 (August 2016) - Won, Young Ju; Lim, Byung Gun; Lee, So Hyun; Park, Sangwoo; Kim, Heezoo; Lee, Il Ok; Kong, Myoung Hoon
Abstract: Background: The surgical pleth index (SPI) is proposed for titration of analgesic drugs during general anesthesia. Several reports have investigated the effect of SPI on the consumption of opioids including remifentanil, fentanyl, and sufentanil during anesthesia, but there are no reports about oxycodone. We aimed to investigate intravenous oxycodone consumption between SPI-guided analgesia and conventional analgesia practices during sevoflurane anesthesia in patients undergoing thyroidectomy. Methods: Forty-five patients undergoing elective thyroidectomy were randomly assigned to an SPI group (SPI-guided analgesia group, n = 23) or a control group (conventional analgesia group, n = 22). Anesthesia was maintained with sevoflurane to achieve bispectral index values between 40 and 60. In the SPI group, oxycodone 1 mg was administered intravenously at SPI values over 50; in the control group, oxycodone 1 mg was administered intravenously at the occurrence of tachycardia or hypertension event. Intraoperative oxycodone consumption and extubation time were recorded. The number of hemodynamic and somatic movement events was recorded, as were postoperative pain and recovery scores. Results: Patients' characteristics were comparable between the groups. Intraoperative oxycodone consumption in the SPI group was significantly lower than the control group (3.5 ± 2.4 vs 5.1 ± 2.4 mg; P = 0.012). Extubation time was significantly shorter in the SPI group (10.6 ± 3.5 vs 13.4 ± 4.6 min; P = 0.026). Hemodynamic and somatic movement events during anesthesia were comparable between the groups, as were numeric rating scales for pain and modified Aldrete scores at postanesthesia care unit. Conclusions: SPI-guided analgesia reduces intravenous oxycodone consumption and extubation time compared with conventional analgesia based on clinical parameters during sevoflurane anesthesia in patients undergoing thyroidectomy.